Assessment of the Efficacy of Thrombolysis (Metalase) in Management of Acute Myocardial Infarction in Relation to Time When it is Given After Onset of MI - Ahmed A Al-Delaimy , Raed; M Athab Al_Missari , Ahmed (Diyala Journal of Medicine, 2019)
Background : Thrombolysis remains the treatment of choice in ST-segment elevation myocardial infarction (STEMI). Efficacy of reperfusion therapy in (AMI) is strictly time-dependent. Most benefit is achieved with initiation of therapy within the first 60–90 min after onset of symptoms. Objectives : The aim of this study is to show the efficacy of the thrombolysis in acute myocardial infarction ( AMI ) in relation to the time (hours ) when it is given after the onset of myocardial infarction . Methods : 56 patients with acute STEMI admitted to coronary care unite (CCU) of baquba teaching hospital were treated with thrombolytic therapy ( metalase) in the period from 1st / October / 2009 to 30th / may / 2010 .We observe the beneficial changes that occur after metalase use in relation to the time at which it is given after onset of myocardial infarction (i.e. onset of characteristic chest pain). Results : From 56 patients , (4) patients ( 7.1%) came with in 1st hour and they develop complete recovery , their ECG return to normal after thrombolysis, ( 23) patients (41% ) came with in 1-6 h. , they develop partial recovery and they had decrease in ST-segment elevation after thrpombolysis, (29) patients (51.7%) came after 6h. were having no any benefit from thrombolysis and had no change in ECG after thrombolysis . Conclusions : Thrombolysis if given early in the 1st few hours (1-6 h.) is useful way to treat cases of STEMI , as it decrease infarct size and decrease morbidity and mortality .